Histopathological Pattern of Endometrial Biopsies in Patients with Abnormal Uterine Bleeding Attending Birat Medical College Teaching Hospital - Kafle, Neeta; Shaukin, Shilpi; Kafle, Santosh Upadhaya; Singh, Mrinalini; Parajuli, Surya Bahadur (Birat Journal of Health Sciences, 2020)
Introduction: Abnormal uterine bleeding (AUB) is one of the commonest gynaecological problems. Etiology of AUB may be structural and functional and varies according to age group. Histological pattern of endometrial sampling along with clinical and radiological findings remains the diagnostic standard for clinical diagnosis of endometrial pathology which ultimately helps in deciding the management of the patients.Objectives: To determine histopathological pattern of endometrial biopsies in patients with AUB attending Birat Medical College Teaching Hospital. To determine the pattern of menstrual abnormality in patients with AUB in different age groups.Methodology: We conducted a prospective hospital based cross sectional study for a period of one year (1 April 2019 to March 31 2020). Histopathological findings of all endometrial biopsy samples in patients with AUB were examined. Patients were categorized into different age groups and the patterns of menstrual abnormality were also documented.Results: 166 patients presenting with AUB underwent endometrial biopsy. Most of them were of perimenopausal age group (42.77%). Menorrhagia was the most common presenting menstrual abnormality. Histopathological examination predominantly revealed normal cyclical endometrium. Hyperplasia was seen more frequently in patients > 40 years of age. Malignancy was diagnosed in 2.41%, all were adenocarcinoma and was seen in > 50 years age.Conclusion: AUB is a common gynaeco-pathological problem with varied clinical presentation and multiple causes. Functional endometrial changes account for the highest histological pattern. However hyperplasia and malignancy are important cause of AUB in perimenopausal and post menopausal age group's women.